Analyzing the Performance of a Signalized 4-Leg Intersection Connecting Jalan Kluang Federal Route (Ft050) – Jalan Sri Bengkal (Johor State Route J125) - Akbar, Ahmad Khairibrahim; Ahmad Termida, Norsitihazlin (Recent Trends in Civil Engineering and Built Environment, 2024)
Malaysia and other emerging countries suffer from traffic congestion. The population expands along with the number of vehicles. When traffic exceeds road capacity, congestion occurs, including at intersections. Delays, pollution, accidents, and increased operational expenses were all caused by congestion. Due to the heavy traffic volume at the signalized intersection of Jalan Sengkuang (J125), this location was chosen for this study. Examining this signalized intersection may helped resolve the congestion. This research evaluated the performance of a signalized intersection at Jalan Kluang Federal Route (FT050)-Jalan Sengkuang (Johor state route J125) in terms of Level of Service (LOS), vehicle delay, and queue length. Data on vehicle volume was recorded using a CountCam2 for the morning, afternoon, and evening peak hours on a weekday and a weekend. Meanwhile, traffic signal timing and road geometric data were measured using laser distance and stop watch. The Signalized and Unsignalized Intersection Design and Research Aid (SIDRA) version 8.0 was used to analyze the data. The critical LOS was LOS F, as determined by SIDRA. LOS F has occurred on the main road connecting West Kluang Road and East Kluang Road, and it has been found on all days and at all peak times.